PERBEDAAN EFISIENSI BANK UMUM KONVENSIONAL : PENDEKATAN DATA ENVELOPMENT ANALYSIS - Agall Cahyadi, Razono; JMV. Mulyadi; Yusuf, Muhammad (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
The purpose of this study was to analyze the efficiency differences between years and between groups of bank BOOKS, to analyze the influence of DEA input factors on the level of efficiency and to analyze the consistency of financial ratios to the efficiency level using the production approach and intermediation approach. This research method uses quantitative method with Data Envelopment Analysis (DEA) approach with production and intermediation approach as measured by program of MaxDEA 6.13. To test year-to-year differences and bank statements, researchers used different Kruskal Wallis and Mann Whitney U test as Post Hoc Test. The results of this study indicate that there is a significant difference between bank BUKU but there is no difference between years, not all input factors DEA affect the level of efficiency and financial ratios consistent with the efficiency in the DEA approach.